The Impact of Organizational Culture on Educational Sector Workers of Paktika Province of Afghanistan - Mohammad Shafiq Hafiz; Abdul Naeem Abdul Basheer (Randwick International of Education and Linguistics Science Journal, 2021)
Organizational culture is a believe system exists among the workers of an organization. Through organizational culture, organizations can be distinguished from each others. It is precious to inform the organization's managers and all workers about the organizational culture. The aim of this study is to find out the presence of organizational culture in educational sector workers of Paktika province of Afghanistan. Daniel Denison's organizational culture model is used in this research. Denison's model has four main aspects (involvement, consistency, adaptability and mission), that an organization must have in order to be an effective organization. In this study, the mixed research method (Quantitative and Qualitative) is used whereas questionnaire and interview tools were used for data collection. The administrative staff of the educational sector of Paktika province (University, Directorate of Education, Directorate of Information and Culture, and Directorate of Olympic), numbering up to 120, has been selected as a statistical population for the research. The results of this research are somehow similar to the previous researches done in Afghanistan. Generally, it is seen that working activities of educational sector staff of Paktika province is influenced by organizational culture. The results of this research show that, based on Denison model of organizational culture, educational sector workers of Paktika province has 65% of effective organizational culture and the mission aspect was potent than other aspects of organizational culture.